KESULITAN PEMBELAJARAN PENJAS ANAK BERKEBUTUHAN KHUSUS TUNAGRAHITA DI SEKOLAH LUAR BIASA KOTA PEKANBARU - Saputra, Andree Dandi; Sulastio, Agus; Rahmatullah, M. Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The aim of this research is to determine the difficulties,implementation of learning, and evaluation of physical education learning for childrenwith special needs for mental retardation in special schools throughout Pekanbaru.This research is classified as descriptive research. This research was carried out at aspecial school in the city of Pekanbaru from the end of June 2023 to December 2023.Based on the results of the research and discussion, physical education learning formentally retarded classes throughout Pekanbaru City took place according to theexisting learning schedule and hours. Teachers teach according to the competenciesthat students must achieve. However, in implementing learning, teachers do not alwaysfind conditions that are conducive to teaching existing basic competencies. The resultsof this research can be concluded as an average of 82.14% with five factors which addup to the very good category. The meaning of very good here is that when comparedwith the interview results, SLB teachers really have difficulty teaching PhysicalEducation, but because they are based on sincere intentions, they are able to teach eventhough it is not according to the learning plan.Key Words: Physical Education Learning Difficulties, Children with Special Needs and Mentally Impaired